Manajemen Komunikasi Digital Pasraman di Media Sosial: Antara Laporan dan Kreativitas Konten - Suardana, I Ketut Putu; Dasih, I Gusti Ayu Ratna Pramesti (Unitri Press, 2025)
Social media has now become an integral part of the communication strategy of religious educational institutions, including Hindu pasraman in Lombok. However, its utilization has not been optimal as a means of education and dissemination of dharma values ​​digitally. Many pasraman still face limitations in managing interesting and relevant content for the younger generation. This study aims to analyze the communication management of pasraman on social media, especially Facebook, by highlighting content patterns, upload intensity, and challenges and opportunities in developing creative communication based on Hindu religion. This study uses a qualitative method through observation of five Facebook accounts of pasraman in Lombok during the period from January to April. Data were analyzed based on content categories and information presentation patterns. The results of the study show that the majority of pasraman still use social media as a space for documenting activities, dominated by uploading photos and reports. Meanwhile, the use of interactive visual formats such as videos, reels, and creative narratives is still very limited. The main challenges include limited human resources, minimal training in digital content management, and cultural resistance to digital transformation. Nevertheless, social media has great potential as an educational and spiritual medium that can strengthen the religious identity of the younger generation of Hindus. Therefore, it is recommended that each pasraman form a social media management team and strengthen community-based digital collaboration to optimize religious communication in the digital era. Abstrak Media sosial kini menjadi bagian integral dari strategi komunikasi lembaga pendidikan keagamaan, termasuk pasraman Hindu di Lombok. Namun, pemanfaatannya belum optimal sebagai sarana edukasi dan diseminasi nilai-nilai dharma secara digital. Banyak pasraman masih menghadapi keterbatasan dalam mengelola konten yang menarik dan relevan bagi generasi muda. Penelitian ini bertujuan untuk menganalisis manajemen komunikasi pasraman di media sosial, khususnya Facebook, dengan menyoroti pola konten, intensitas unggahan, serta tantangan dan peluang dalam pengembangan komunikasi kreatif berbasis keagamaan Hindu. Penelitian ini menggunakan metode kualitatif melalui observasi terhadap lima akun Facebook pasraman di Lombok selama periode Januari hingga April. Data dianalisis berdasarkan kategori konten dan pola penyajian informasi. Hasil penelitian menunjukkan bahwa mayoritas pasraman masih menggunakan media sosial sebagai ruang dokumentasi kegiatan, didominasi oleh unggahan foto dan laporan. Sementara itu, pemanfaatan format visual interaktif seperti video, reels, dan narasi kreatif masih sangat terbatas. Tantangan utama mencakup keterbatasan sumber daya manusia, minimnya pelatihan pengelolaan konten digital, dan resistensi kultural terhadap transformasi digital. Meskipun demikian, media sosial memiliki potensi besar sebagai wahana edukatif dan spiritual yang dapat memperkuat identitas keagamaan generasi muda Hindu. Oleh karena itu, disarankan agar setiap pasraman membentuk tim pengelola media sosial dan memperkuat kolaborasi digital berbasis komunitas untuk mengoptimalkan komunikasi keagamaan di era digital.